2016
DOI: 10.1021/acs.orglett.6b01032
|View full text |Cite
|
Sign up to set email alerts
|

Access to Structurally Diverse Quinoline-Fused Heterocycles via Rhodium(III)-Catalyzed C–C/C–N Coupling of Bifunctional Substrates

Abstract: Rhodium(III)-catalyzed C-H activation of heteroarenes and functionalization with bifunctional substrates such as anthranils allows facile construction of quinoline-fused heterocycles under redox-neutral conditions. The couplings feature broad substrate scope and provide step-economical access to two classes of quinoline-fused condensed heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(40 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“… 758 , 759 The same reaction was also shown to occur on 2-pyridones ( Scheme 125D ). 759 Interestingly, the cyclisation did not occur when phenyl or thienyl substrates were investigated, and the reaction only resulted in the corresponding o -formylaniline-substituted product ( Scheme 125B ). 758 …”
Section: Heterocyclic Dgs In C–h Functionalisationmentioning
confidence: 73%
See 2 more Smart Citations
“… 758 , 759 The same reaction was also shown to occur on 2-pyridones ( Scheme 125D ). 759 Interestingly, the cyclisation did not occur when phenyl or thienyl substrates were investigated, and the reaction only resulted in the corresponding o -formylaniline-substituted product ( Scheme 125B ). 758 …”
Section: Heterocyclic Dgs In C–h Functionalisationmentioning
confidence: 73%
“… 757 The use of anthranils (2,1-benzisoxazoles) as alternative, more stable nitrene precursors was independently reported by Wang and Li. 758 , 759 The reaction of indoles with anthranils using polar protic solvents (H 2 O or MeOH) and Rh catalysis resulted in a tandem amination–cyclisation process, leading to the formation of indoloquinolines ( Scheme 125C ). 758 , 759 The same reaction was also shown to occur on 2-pyridones ( Scheme 125D ).…”
Section: Heterocyclic Dgs In C–h Functionalisationmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] These aromatic compounds have agood coordinating propensity and contain aw eak N À Ob ond, and these features lead to facile ring-opening under transition-metal catalysis.T od ate,afew reports have shown that, with transition-metal catalysts,a nthranils could either function as electrophilic amination reagents (Scheme 1a) [2] or proceed through transannulation to form other aromatic rings (Scheme 1b). [1] These aromatic compounds have agood coordinating propensity and contain aw eak N À Ob ond, and these features lead to facile ring-opening under transition-metal catalysis.T od ate,afew reports have shown that, with transition-metal catalysts,a nthranils could either function as electrophilic amination reagents (Scheme 1a) [2] or proceed through transannulation to form other aromatic rings (Scheme 1b).…”
mentioning
confidence: 99%
“…Anthranil and its derivatives are important chemical feedstocks for the synthesis of pharmaceuticals and functional molecules. [1] These aromatic compounds have agood coordinating propensity and contain aw eak N À Ob ond, and these features lead to facile ring-opening under transition-metal catalysis.T od ate,afew reports have shown that, with transition-metal catalysts,a nthranils could either function as electrophilic amination reagents (Scheme 1a) [2] or proceed through transannulation to form other aromatic rings (Scheme 1b). [3] Catalytic asymmetric dearomatization (CADA) reactions provide au seful strategy for the transformation of planar aromatic compounds into enantioenriched chiral cyclic molecules.…”
mentioning
confidence: 99%